TEACHERS’ PERCEPTIONS ON ICT INTEGRATION IN TVET CLASSES: A CASE STUDY IN KHARTOUM STATE-SUDAN - Ramadan, Abdelmoiz; Chen, Xiaohui (PEOPLE: International Journal of Social Sciences, 2018)
Information and communication technology ICT has been strongly admissible used in teaching and learning process in the world. In Sudan, despite the Federal Ministry of General Education FMGE policy plan encourages the use of ICT in the education sector to advance the education system as one of the state’s sectors. Apart from the FMGE policy plan to integrate ICT in education sector still, there is no progression of ICT in general education. Many factors hindered the integration of ICT in technical and vocational education and training TVET system particularly. Therefore, this study investigated the teachers’ perceptions of ICT integration in TVET classes. The interviews used for collecting data from (10) teachers in Khartoum state. The results revealed that there is no clear ICT policy in education, the lack of physical, and ICT infrastructures, and lack of support in using ICT in TVET from the educational management. The findings imply that the government should increase efforts on ICT integration and also should involve various education stakeholder including teachers, the overall process of ICT integration in the TVET system. Additionally, international experiences are highly recommended to propose private ICT policy and, the modern digital learning materials might be equipped in TVET classrooms.